Some Taxonomic Elements of the Internal Control of Public Finances and Experiences of Teaching them at the University of Public Service - Lentner, Csaba (Public Finance Quarterly, 2022)
The study focuses on internal control within the area of public finance control, the comprehensive reform of which started in 2010. The aim is to draw attention to the legal background of the internal controls of budgetary organisations and how to improve the efficiency of the use of public funds. The paper addresses in detail the requirements arising from European and Hungarian legal standards, the connection with other control aggregates of public finances and taxonomic relationships. The study outlines the regulation and methodological background of internal audit. An additional unique feature of the study is that it presents the educational system of fiscal and internal audit training for government officials at the National University of Public Service and the scientific summary of experiences resulting from the questionnaire survey of graduates.